Effect of thermo-mechanical ageing on materials and interface properties in flexible microelectronic devices. (July 2021) - Chapel, Anthony; Fortineau, Jérôme; Porcher, Nicolas; Malandain, Simon; Boucaud-Gauchet, Séverine
Abstract: The effect of thermal ageing, fatigue and thermo-mechanical ageing on flexible microelectronic devices is studied and reported from a materials and functional durability perspective. The degradation mechanisms of encapsulant and substrate were both studied. Property changes in encapsulant and substrate materials are analyzed and their relationships in the failure mechanisms of the flexible devices determined. Stiffening of the resin under thermal ageing conditions is associated with delamination in test vehicles, which leads to a loss of functional electrical properties. Degradation was due to the prominence of crosslinking reactions occurring during thermal oxidation at 120 °C. A moderate stiffening of the resin occurs after fatigue stress testing. Whereas this latter stiffening is similarly associated with crosslinking reactions, here, stiffening could not be induced by thermal degradation of the resin, because the stress frequency employed was low. Instead thermo-mechanical coupling occurred in two stages. Under mild conditions, the degradation mechanisms correspond to the combined effect of thermal ageing and fatigue processes. Under harsher thermo-mechanical conditions, the chain-scission mechanisms become more efficient and induce a softening of the resin. Highlights: Flexible microelectronics test-vehicles were encapsulated with an epoxy resin. The durability of the encapsulation was studied regarding the materials ageing. Effect of thermo-mechanical coupling on the epoxy resin properties was evaluated. Thermo-mechanical coupling occurred in two step. Chain-scission reactions are linked with delamination.